2004
DOI: 10.1002/mrd.20090
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptional activation of the membrane‐bound progesterone receptor (mPR) by dioxin, in endocrine‐responsive tissues

Abstract: We originally identified the membrane-bound progesterone receptor (mPR) using a screening for genes differentially expressed in liver of rats exposed to dioxin. Recent findings have suggested a role for the mPR in sperm cells, ovary, and brain; however, its mechanisms of action are largely unknown. In this study, we examined the expression pattern of the mPR in liver of rats exposed to dioxin and identified possible mechanisms of its regulation. We observed that mPR expression was induced by dioxin, but was al… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
22
0

Year Published

2006
2006
2012
2012

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 22 publications
(22 citation statements)
references
References 29 publications
0
22
0
Order By: Relevance
“…Thiele and colleagues from the Max Planck Institute of Molecular Cell Biology and Genetics in Dresden demonstrated that transfected PGRMC1 was induced to form crosslinked homodimers with high efficiency upon illumination of cells grown in the presence of photo-activatable amino acid precursors [50], although they did not examine the presence of cysteine disulfides. To confuse the seemingly simple conclusion that the 56 kDa form of PGRMC1 always represents a disulfide linked dimer, Selmin et al [1] observed an immunologically defined PGRMC1 band with apparent molecular weight of 50 kDa which was observed under reducing conditions, "therefore it is unlikely that the 50 kDa band might be a dimer of the 25 kDa protein detected in the liver." [1].…”
Section: Interaction Partnersmentioning
confidence: 93%
See 2 more Smart Citations
“…Thiele and colleagues from the Max Planck Institute of Molecular Cell Biology and Genetics in Dresden demonstrated that transfected PGRMC1 was induced to form crosslinked homodimers with high efficiency upon illumination of cells grown in the presence of photo-activatable amino acid precursors [50], although they did not examine the presence of cysteine disulfides. To confuse the seemingly simple conclusion that the 56 kDa form of PGRMC1 always represents a disulfide linked dimer, Selmin et al [1] observed an immunologically defined PGRMC1 band with apparent molecular weight of 50 kDa which was observed under reducing conditions, "therefore it is unlikely that the 50 kDa band might be a dimer of the 25 kDa protein detected in the liver." [1].…”
Section: Interaction Partnersmentioning
confidence: 93%
“…In the 2001 paper, Falkenstein et al [15] showed that the 56 kDa form from swine liver could be reduced to a 28 kDa form in the presence of dithiothreitol (DTT), a reducer of disulfide bonds. Selmin, one of the original authors on the 25-Dx cloning, also referred to dioxin induced rat 25-Dx as mPR in 2005 [1].…”
Section: Mprmentioning
confidence: 98%
See 1 more Smart Citation
“…Briefly, reactions were run at a final volume of 25 AL consisting of the following master mix: 2.5 AL of 10Â SybrGreen buffer, 3 AL of 25 mmol/L MgCl 2 , 2 AL of 12 mmol/L deoxynucleotide triphosphates (dATP, dCTP, dGTP, and dTTP), 2 AL each of forward and reverse primers, 0.25 AL Amperase Uracil-N-glycosylase, 0.125 AL Taq polymerase, 11.125 AL nuclease free doubledistilled water, and 2 AL DNA. The ABI 5700 sequence detection system and comparative C T method were used to quantify the relative differences in PCR product as described previously (34). BRCA-1 promoter amplicons were normalized to input.…”
Section: Methodsmentioning
confidence: 99%
“…Umbreit andGallo 1988, Safe andKrishnan 1995). They exert estrogenic effects through ER signalling modulated by the AhR (Ohtake et al 2003, Selmin et al 2005, cf. Pliskova et al 2004.…”
Section:  Effects Assessment 4 423 Reproductive Effectsmentioning
confidence: 99%